2004
DOI: 10.1074/jbc.m408154200
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacochaperones Post-translationally Enhance Cell Surface Expression by Increasing Conformational Stability of Wild-type and Mutant Vasopressin V2 Receptors

Abstract: Some membrane-permeable antagonists restore cell surface expression of misfolded receptors retained in the endoplasmic reticulum (ER) and are therefore termed pharmacochaperones. Whether pharmacochaperones increase protein stability, thereby preventing rapid degradation, or assist folding via direct receptor interactions or interfere with quality control components remains elusive. We now show that the cell surface expression and function (binding of the agonist) of the mainly ER-retained wild-type murine vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 25 publications
(42 reference statements)
9
123
0
Order By: Relevance
“…4)(10-12, 17). The absence of translocation of V2R mutants to the cell surface is further supported by the fact that cAMP responses are obtained within 10 min following agonists addition, whereas it takes V2R antagonists 4-8 h to insert V2R mutants in the plasma membrane (11,23). Our data are different from those of Petaja-Repo et al (24), who found that nonpeptide agonists were able to stabilize the expression and maturation of ER-retained wild-type ␦-opioid receptor (DOR).…”
Section: Intracellular Activation Of V2r Mutants In Ndi Does Not Chanmentioning
confidence: 76%
“…4)(10-12, 17). The absence of translocation of V2R mutants to the cell surface is further supported by the fact that cAMP responses are obtained within 10 min following agonists addition, whereas it takes V2R antagonists 4-8 h to insert V2R mutants in the plasma membrane (11,23). Our data are different from those of Petaja-Repo et al (24), who found that nonpeptide agonists were able to stabilize the expression and maturation of ER-retained wild-type ␦-opioid receptor (DOR).…”
Section: Intracellular Activation Of V2r Mutants In Ndi Does Not Chanmentioning
confidence: 76%
“…The present study is a needed antecedent to selection of the appropriate time for pulsatile administration of pharmacoperones in vivo and suggests that, at least in the case of GnRH receptor mutants with three chemical classes of pharmacoperones, the drug need not be present at the time of synthesis, as appears to be the case for other vasopressin receptor subtypes (Hawtin, 2006;Morello et al, 2000;Wuller et al, 2004). The present model suggests that pharmacoperones act post-translationally to aid in receptor folding.…”
Section: Discussionmentioning
confidence: 88%
“…Recent evidence suggests that the ER quality control does not only target permanently misfolded proteins to ERAD but may also dispose some folding competent ones, possibly due to their slow folding kinetics. This applies also to several polytopic membrane proteins, including G protein-coupled receptors (GPCRs; Petäjä-Repo et al, 2000;Imai et al, 2001;Lu et al, 2003;Wü ller et al, 2004;Pietilä et al, 2005). Thus, export from the ER is the limiting step in their expression and probably provides a mean to regulate the number of functional receptors at the cell surface.…”
Section: Introductionmentioning
confidence: 99%